(untitled) (International Seven Journal of Health Research, 2023)
Dysphagia is frequent in the elderly population, especially in individuals with COVID-19. The aim of this integrative review was to elucidate the connection between dysphagia and COVID-19 in the elderly, focusing on the implications arising from it and associated comorbidities. Methods: A comprehensive search using the PICO strategy was conducted in six databases: PubMed/Medline, Embase, LILACS, Scopus, Web of Science, and SpeechBITE. Articles published between 2019 and 2022, without language restrictions, involving participants aged 60 years or older diagnosed with COVID-19 and exhibiting signs/symptoms of dysphagia were included. Results: The analysis included 42 articles, with the majority being case reports. The sample involved 298 older adults, with a mean age of 70.5 years and a predominance of males. The implications of dysphagia included the need for alternative feeding, laryngotracheal penetration/aspiration, adjustment in diet consistency, aspiration pneumonia and dysfunction in the orofacial and pharyngeal muscles. Pre-existing comorbidities associated with COVID-19 were identified, such as Guillain-Barré Syndrome, Myasthenia Gravis, Hypertension and Diabetes Mellitus. Conclusion: This integrative review highlights several implications of dysphagia in the elderly with COVID-19, with alternative feeding being the most mentioned. However, less than half of the studies described the implications observed among patients. The findings highlight the need for future investigations and development of appropriate therapeutic strategies aimed at improving quality of life and preventing complications in this population. Identification of the implications and comorbidities associated with dysphagia may assist in the development of more effective and safer clinical management approaches. DOI:https://doi.org/10.56238/isevjhv2n2-017